Hyper-IgE syndrome caused by DOCK8 mutation with a tumour-like lesion of the lip: a case report. Issue 12 (December 2022) - Zhu, W.-X.; Liu, Y.-Y.; Hua, H.; Yu, G.-Y.
Abstract: Autosomal recessive hyper-IgE syndrome caused by DOCK8 gene mutation is an immunodeficiency. However, the presentation of a tumour-like lesion of the lip in autosomal recessive hyper-IgE syndrome has not yet been reported. This article reports the case of a 20-year-old man with autosomal recessive hyper-IgE syndrome who presented with a tumour-like lesion of the lip, and hyperplasia and erosion of the gingiva. The clinical manifestations included coarse face and neck skin, a diffuse tumour-like lesion on the upper lip showing a reddish erosive nodular surface with yellowish-white exudation, erosive buccal mucosa, and severe periodontitis. The swollen gingival and palatal mucosa indicated nodular hyperplasia and redness with pseudomembrane. The patient had a significantly increased peripheral blood eosinophil count and serum IgE level and an abnormal T lymphocyte count. His oral lesions improved markedly after prednisolone acetate use and local symptomatic treatment for 2 years. However, the patient unfortunately died of a cerebral infection 6 months after the oral lesions had resolved. The novel features of the labial tumour-like lesion described here extend our understanding of the manifestations of autosomal recessive hyper-IgE syndrome.